Lingual Investigation of President Soekarno Speech: A Report (e-Journal of Linguistics, 2019)
The current research aims at investigating the most important speech of Soekarno andthe ideologies behind the speech. Since Soekarno was the proclaimer of Indonesianindependence as well as the first president of Indonesia, we would claim that his speeches wereimportant to be investigated. Among the speeches, we tried to reveal the most important onethrough a lingual investigation. This investigation was based on grounded theory andhermeneutic theory. It was focused on the text as a part of the language. The results have shownthat the most important speech of Soekarno is the speech entitled, ‘Tahun Berdikari’. It is viewedas a high novelty finding because there is no researcher who has ever claimed ‘Tahun Berdikari’as the most important speech in the history of Indonesia. The speech contained three mainideologies, namely (1) unity as the most important thing for Indonesians, (2) revolution must bein the Indonesian soul, and (3) imperialism and capitalism as Indonesia’s main enemy.
Keywords: Soekarno’s Speech; Discourse; Grounded Theory; Hermeneutics